Sintesis Natrium Silikat Menggunakan Silika dari Pasir Pantai Bengkalis - Azis, Yelmida; Ida Zahrina; Mutamima, Anisa; Alfarisi, Cory Dian; Nurfatihayati (Jurnal Riset Kimia, 2024)
Sodium silicate (Na2SiO3) is a chemical industrial material that is widely used as a metal cleaner, adhesive, and as a filler in the detergent, soap and toothpaste industries. Sodium silicate can be synthesized from silica dioxide (SiO2), which can be obtained through an extraction process from materials containing silica such as sand, glass bottle waste or rice husks. In this research, the synthesis of Na2SiO3 was carried out using silica extracted from Bengkalis beach sand using the acid leaching method, with a 3M HCl solution. The results of X-ray fluorescence (XRF) analysis of Bengkalis Beach sand showed that the silica content reached 89.1%. This research aims to determine the effect of the molar ratio of the NaOH reactant to the extracted SiO2 (2:1, 3:1 and 4:1) on the Na2SiO3 produced. The synthesis of Na2SiO3 was carried out using the hydrothermal method at atmospheric pressure, by reacting a 4M NaOH solution with 10 g of silica from Bengkalis sand, by heating at 110oC for an hour and stirring at 600 rpm. A molar ratio of 2:1 is the best ratio which produces 9.427g of Na2SiO3. From analysis using Fourier Transform Infrared (FTIR) spectroscopy, the spectrum patterns obtained are suitable for compounds containing silanol (≡Si-OH) and siloxane (≡Si-O-Si≡) groups. The X-ray diffraction (XRD) pattern of the synthesized compound is in accordance with standard sodium silicate. The Na2SiO3 obtained has a crystal diameter of 44.8 nm with an agglomerate-shaped morpology.